2015
DOI: 10.1108/jpif-11-2014-0069
|View full text |Cite
|
Sign up to set email alerts
|

Outperforming the benchmark: online information demand and REIT market performance

Abstract: Purpose – The purpose of this paper is to investigate whether there is a relationship between asset-specific online search interest and movements in the US REIT market. Design/methodology/approach – The authors collect search volume (SV) data from “Google Trends” for a set of keywords representing the information demand of real estate (equity) investors. On this basis, the authors test hypothetical investment strategies based on changes … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 59 publications
(83 reference statements)
1
12
0
Order By: Relevance
“…They find that search volume index of certain keywords like 'Home Finance' is positively correlated to the volatility of the index comprising real estate stocks in India. Rochdi and Dietzel (2015) show in their study that online information seeking behavior can predict future price movements of US REITs.…”
Section: Extant Literaturementioning
confidence: 97%
“…They find that search volume index of certain keywords like 'Home Finance' is positively correlated to the volatility of the index comprising real estate stocks in India. Rochdi and Dietzel (2015) show in their study that online information seeking behavior can predict future price movements of US REITs.…”
Section: Extant Literaturementioning
confidence: 97%
“…The study of the attention effect is not limited only in stock markets and the results in other markets largely confirm the findings in stock markets. See, for example, Goddard et al (2015) for foreign exchange markets, Li et al (2015) for energy markets, and Rochdi and Dietzel (2015) and Braun (2016) for real estate markets. reveals information to asset prices.…”
mentioning
confidence: 99%
“…one of the first research papers is Hohenstatt et al in (2011). Following on from that work, Rochdi and Dietzel (2015) and Braun (2016) found that Google-augmented models improve the predictability of REIT market movements and volatility.…”
Section: Literature Reviewmentioning
confidence: 97%